Metaphorical Conceptual of Sadness Emotion in Bruno Mars’ Song - Corenia Sagista; Michelle Andrea Mursalim; Kumala, Sonya Ayu (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2023)
This research is about the sadness metaphor that found in Bruno Mars’ song. Bruno Mars is one of the famous singer from USA. As a singer also song writer Bruno Mars not only depending on one theme of the songs but variety. From all his songs, the most popular is some sad songs theme. According (Lakoff,G & Johnson,M, 2003 ), conceptual metaphor is an understanding and expressing one kind of thing in terms of another. Based on the theory of (Barcelona, 1986 )Metaphors of sadness were analyzed from a cognitive linguistic perspective. He identified there are 14 sources domains in sadness metaphor. The writer would like to observes sadness metaphor used the lyrics of the songs. Bruno Mars’ songs were chosen as the data sources because there are many of his songs have lyrics that contains sad feeling. This research used qualitative research approach. As a result, the researcher found there are some fragments of the lyrics in Bruno Mars’ songs which categorized into 5 types of source domains in sadness metaphor, which are: SAD IS DOWN, SAD IS DARK, SADNESS IS A NATURAL FORCE, SADNESS IS A BURDEN and SADNESS IS INSANITY. The most dominant sources domains of sadness metaphor that is found in Bruno Mars’ song is sadness is a burden.